Dream and Reality in the Life of Nicholas Lochoff: on the History of the Creation of Nicholas Lochoff’s Pittsburgh Cloister - Katz, Naum Gregory (Przegląd Wschodnioeuropejski, 2019)
This article recounts the unusual fate of the artist-copyist Nicholas Lochoff. Lochoff, who lived most of his life abroad, in Italy, remains relatively unknown in his Russian homeland. Based on Russian and American historiography, and the periodical press, the author follows Lochoff ’s path from professional revolutionary to self-taught artist who became recognized as one of the leading copyists of the twentieth century. As research shows, the philanthropy of Helen Clay Frick enabled the University of Pittsburgh to acquire Lochoff ’s unclaimed copies of European masterpieces where they became an asset in educating future generations of American art historians.